2016
DOI: 10.1002/ejic.201501400
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural and Spectroscopic Characterization of CrIII, FeIII, CoIII, NiII and CuII Complexes with an Asymmetric 1,3,4‐Thiadiazole Ligand

Abstract: The reaction of the new asymmetric 1,3,4-thiadiazole-based ligand 2-[(5-ethylthio-1,3,4-thiadiazol-2-yl)hydrazonomethyl]phenol (H 1 ETHP) with various third-row transition metal salts resulted in the formation of six new mononuclear complexes [Cr(ETHP) 2 ]ClO 4 (1), [Fe(ETHP) 2 ][FeCl 4 ] (2), [Co(ETHP)(ETHP -H )] (3), [Ni(ETHP)(H 1 ETHP)]Cl (4), [Ni(ETHP)(H 1 ETHP)](ClO 4 ) (5), [Ni(ETHP)(H 1 ETHP)]Br (6), and one tetranuclear complex [Cu 2 Cl 3 (ETHP)(H 1 ETHP)] 2 (7). H 1 ETHP and all complexes have been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The observed Fe−N(H) distances correspond to the high spin state of the complex according to the literature data for the octahedral FeN 4 O 2 complexes with different ligands [30] . Up to date, the only two Fe complexes with modified thsa chelating ligands in FeN 4 O 2 coordination mode are known [31,32] . They both are high‐spin and also have similar Fe−N/O bond lengths as in 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed Fe−N(H) distances correspond to the high spin state of the complex according to the literature data for the octahedral FeN 4 O 2 complexes with different ligands [30] . Up to date, the only two Fe complexes with modified thsa chelating ligands in FeN 4 O 2 coordination mode are known [31,32] . They both are high‐spin and also have similar Fe−N/O bond lengths as in 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[30] Up to date, the only two Fe complexes with modified thsa chelating ligands in FeN 4 O 2 coordination mode are known. [31,32] They both are high-spin and also have similar FeÀ N/O bond lengths as in 2. An additional evidence of the HS state of the complex 2 is given by an essential distortion within the coordination Fe III octahedron (NÀ FeÀ O and NÀ FeÀ N angles are far from 180°, Table S3; the distortion parameter Σ, which is a measure of the net angular deviation from the idealized octahedral geometry, equals 118.1/ 116.9°for two molecular sites, Table S4).…”
Section: Crystal Structure Of Dimer 2•3h 2 Omentioning
confidence: 94%
“…Their diverse biological activity possibly arises from the presence of the NCS moiety in the molecule (Oruç et al, 2004). An interesting feature of the metal-ligand chemistry of these compounds is that the complexes can be either mononuclear (Tzeng et al, 2004;Varna et al, 2018;Qiu et al, 2014) or binuclear (Deckert et al, 2016;Ardan et al, 2017). A search of the Cambridge Structural Database (CSD Version 5.4, update of February 2019; Groom et al, 2016) revealed that although crystal structures have been reported for complexes of either 1,3,4-thiadiazole derivatives or OAc with a number of metal ions, including zinc, copper, nickel, manganese, cadmium, cobalt and palladium, no examples are known of mixed-ligand metal complexes containing both 1,3,4-thiadiazole derivatives and OAc.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Besides, the structural characterization of the thiadiazole‐metal complexes have also been studied. Rentschler et al reported the cooperation of the asymmetric 1,3,4‐thiadiazole‐based ligand with third‐row transition metal salts (Cr III , Fe III , Co III , Ni II and Cu II ) . Bharty et al defined the square‐planar geometry of the 2‐mercapto‐5‐methyl‐1,3,4‐thiadiazole palladium(II) compound .…”
Section: Introductionmentioning
confidence: 99%